2009
DOI: 10.1016/j.immuni.2009.03.013
|View full text |Cite|
|
Sign up to set email alerts
|

Sequential Polarization and Imprinting of Type 1 T Helper Lymphocytes by Interferon-γ and Interleukin-12

Abstract: Differentiation of naive T lymphocytes into type I T helper (Th1) cells requires interferon-gamma and interleukin-12. It is puzzling that interferon-gamma induces the Th1 transcription factor T-bet, whereas interleukin-12 mediates Th1 cell lineage differentiation. We use mathematical modeling to analyze the expression kinetics of T-bet, interferon-gamma, and the IL-12 receptor beta2 chain (IL-12Rbeta2) during Th1 cell differentiation, in the presence or absence of interleukin-12 or interferon-gamma signaling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
211
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 236 publications
(220 citation statements)
references
References 40 publications
7
211
0
2
Order By: Relevance
“…Interestingly, IFN-g-induced activation of STAT1 was not sufficient to induce significant expression of Ifng (Fig. 3A), unlike shown previously in naïve Th cells [20,24]. Stimulation with IFN-g did not change the expression level of RORgt but resulted in a detectable increase of T-bet expression as assessed by intracellular immunofluorescence (Fig.…”
mentioning
confidence: 47%
See 1 more Smart Citation
“…Interestingly, IFN-g-induced activation of STAT1 was not sufficient to induce significant expression of Ifng (Fig. 3A), unlike shown previously in naïve Th cells [20,24]. Stimulation with IFN-g did not change the expression level of RORgt but resulted in a detectable increase of T-bet expression as assessed by intracellular immunofluorescence (Fig.…”
mentioning
confidence: 47%
“…In vitro-generated Th17 cells responded to IL-12, by phosphorylation of STAT4 in all cells (Fig. 1C), and expression of IFN-g by more than 40% of the cells ([17] and data not shown).To confirm that downregulation of IL-12Rb2 chain expression is not a transient consequence of TCR activation [20,21], we directly isolated splenic Th cells based on the surface expression of IL-12Rb2 ( Fig. 2A, gating for viable CD4 1 Th cells shown in Supporting Information Fig.…”
mentioning
confidence: 73%
“…Ever since the original classification of circulating memory CD4 T cells into Th1 and Th2 cells,82 functional compartmentalization of antigen‐experienced T cells has become a favorite exercise of immunologists 83, 84, 85. We have shown that GATA3 mediates the epigenetic imprinting of the interleukin‐4 ( Il4 ) gene,86, 87 and how imprinting of the interferon‐γ ( Ifng ) gene is induced by STAT4 88, 89. Most importantly, we and others have shown that imprinting of cytokine genes in activated naive T cells but not in memory T cells requires progression through the S phase of the first cell division.…”
Section: Circulating Memory T Lymphocytesmentioning
confidence: 99%
“…22,23 Here, we extend an established model for master transcription factors with epigenetic processes to investigate the differentiation, memory formation and plasticity of helper T cells. Helper T-cell differentiation has been studied extensively using mathematical models, 9,10,[24][25][26][27][28][29][30][31] but to the best of our knowledge, this is the first attempt to combine genetic and epigenetic levels of regulation in mechanistic models for cellular differentiation. Using analytical and numerical approaches, we show that cell division during clonal expansion markedly increases the speed of differentiation into functional helper T cells.…”
mentioning
confidence: 99%